Assessment of changes in the level of human capital in Poland in the context of the use of European funds for projects in the field of science and education contracted for implementation in 2004–2006 - Sikora-Gaca, Małgorzata; Kosowska, Urszula (Wydawnictwo Naukowe WNPiD UAM, 2019)
The article presents the analysis of 2,947 projects in the area of science and education co-financed by the Structural Funds in Poland in 2004–2006. It summarizes the investments co-financed by the European Regional Development Fund, the European Social Fund and the European Agricultural Guidance and Guarantee Fund. Data on 2,947 projects, with their regional division, have been verified. Thanks to this regional leaders have been distinguished in terms of the number of projects and raised funds in 2004–2006. Most importantly, the amount of the subsidy from the EU to projects in the area of science and education in Poland in the years 2004–2006 has been estimated per capita of individual region. These data were compared with the selected human capital development indicators in 2003, 2006, 2009 and 2012 to assess the impact of European funding in the field of science and education on human capital in Poland.

W artykule przeanalizowano 2947 projektów z obszaru nauki i edukacji realizowanych przy udziale funduszy strukturalnych w Polsce, w latach 2004–2006. Podsumowano inwestycje współfinansowane z Europejskiego Funduszu Rozwoju Regionalnego, Europejskiego Funduszu Społecznego i Europejskiego Funduszu Orientacji i Gwarancji Rolnej. Zweryfikowano dane dotyczące 2947 projektów w podziale na poszczególne województwa. Dzięki temu wyodrębniono regionalnych liderów pod względem liczby złożonych projektów i pozyskanych środków finansowych w latach 2004–2006. Określono kwotę dotacji z UE do projektów z obszaru nauki i edukacji w Polsce per capita. Dane te skonfrontowano z wybranymi wskaźnikami rozwoju kapitału ludzkiego w latach 2003, 2006, 2009 i 2012 w celu oceny wpływu funduszy europejskich w obszarze nauki i edukacji na poziom kapitału ludzkiego w Polsce.
Ocena zmian poziomu kapitału ludzkiego w Polsce w kontekście wykorzystania funduszy europejskich na projekty z zakresu nauki i edukacji zakontraktowane do realizacji w latach 2004–2006
Keywords: Poland; science and education; structural fund; human capital; Polska; nauka i edukacja; fundusze strukturalne; dofinansowanie; kapitał ludzki